Product representations in conjoint analysis in an LMIC setting: Comparing attribute valuation when three-dimensional physical prototypes are shown versus two-dimensional renderings. (2021) - Coulentianos, Marianna J.; Arezoomand, Mojtaba; Chou, Suzanne; Austin-Breneman, Jesse; Adhvaryu, Achyuta; Nambunmee, Kowit; Neitzel, Richard; Sienko, Kathleen H.
Abstract: Conjoint experiments (CEs) provide designers with insights into consumer preferences and are one of several user-based design approaches aimed at meeting users' needs. Traditional CEs require participants to evaluate products based on two-dimensional (2D) visual representations or written lists of attributes. Evidence suggests that product representations can affect how participants perceive attributes, an effect that might be exacerbated in a Low- and Middle-Income Country setting where CEs have seldom been studied. This study examined how physical three-dimensional (3D) prototypes and 2D renderings with written specifications of attribute profiles generated differences in estimated utilities of a CE about a hypothetical new tool for electronic-waste recycling, among workers in North-Eastern Thailand. Two independent CEs were performed with each representation form. Ninety participants across both experiments each ranked three sets of five alternative tool concept solutions from most to least preferred. The results of the conjoint analysis guided the design of a tool optimized for user preferences, which was then distributed to half of the sample through a Becker-DeGroot-Marschak auction experiment. One month after the auction, participants completed an endline survey. The results point toward potential differences in relative importance of different product attributes based on product representation. Price was found to have no significant impact on the valuation of tools in either experiment. The differences in relative importance of product attributes may have been explained by the limitations of 2D renderings for conveying sizes. Further research is needed to understand the impact of product representation on preferences in this context. We recommend careful consideration for product representations – specifically, how well the representations convey all product attributes being evaluated – in CEs. Using a combination of 2D renderings and 3D product features might have satisfied both the speed and low-cost advantages of renderings while enabling participants to have a better sense of product features. Highlights: The relative rating of product attributes changed as a function of prototype form. After one month of product usage, participants' preferences changed. Price had no significant impact on the valuation of products. 3D prototypes may be preferred for evaluation of sizing specifications. 2D renderings may be preferred for evaluation of feature inclusion.